Introduction to .NET MAUI : building cross-platform applications for desktop and mobile devices by using .NET (Apress, 2023)
Build applications for any desktop or mobile operating system by using .NET MAUI - a cross-platform software development framework. This video will teach you how to use .NET MAUI, which is a .NET-based framework for cross-platform native application development. The framework allows you to build applications for Windows, Mac OS, iOS and Android by using the same codebase. The video starts with a short introduction about .NET MAUI and overall contents the author will discuss. You will then demonstrate how to install the necessary development tools that are needed to work with MAUI project templates followed by components of MAUI project structure. Moving forward, you will go through MAUI Blazor project template and learn XAML syntax along with implementation of various UI components. Next, you will learn the importance of Model-View-View-Model architectural pattern in MAUI and demonstrate how to build Windows applications. Towards the end, you will build iOS and Mac OS applications by using MAUI. After going through the video, you will be able build applications in Windows, Mac and iOS using MAUI.